Social Skills Instruction for Urban Learners with Emotional and Behavioral Disorders: A Culturally Responsive and Computer-Based Intervention. (August 2016) - Robinson-Ervin, Porsha; Cartledge, Gwendolyn; Musti-Rao, Shobana; Gibson, Lenwood; Keyes, Starr E.
This study examined the effects of culturally relevant/responsive, computer-based social skills instruction on the social skill acquisition and generalization of 6 urban African American sixth graders with emotional and behavioral disorders (EBD). A multiple-probe across participants design was used to evaluate the effects of the social skills intervention on following adult directions. Results revealed increases in students following adult directions in the treatment phases; however, generalization results were modest for four students. These results support the use of a social skill package consisting of computer-based instruction and culturally responsive materials for urban adolescents with EBD. The specific components of this intervention are discussed along with implications for future research and study limitations.